Notes on poetry and autobiography (From the reading of Antonio Gamoneda) (XXI Century. Spanish Literature and Culture, 2008)
In this article, Miguel Casado separates from the poet Antonio Gamoneda to emphasize the tension between the poetry understood as ¨musical score¨ of an autobiography and self-referential writing.  Casado observes that the clash between these two poles is produced throughout the entire Gamonedian work (Descripción de la mentira, Esta luz, Arden las pérdidas etc.).   He explains the autobiographical conception of Gamoneda´s poetry as the root of the existential, rejecting the realistic representation as much as the fictitious.  Casado carries out an interesting analysis about the existent fissure between life and word, through which fiction would penetrate in the form of myth.  In addition, precisely, it is detained in the process of mythic elaboration through a recurrent character in the work of Gamoneda, ¨the watchman of the snow.¨
Keywords: Poetry; autobiography; self-referential; self-; self-expression; existencial root